Association Between HPV Circulating Tumor DNA and Prognostic Inflammatory Indices in Oropharyngeal Squamous Cell Carcinoma: A Pilot Study - Ryan S. Ziltzer; Zulkifl I. Jafary; Connor Hunt; Iraj Hasan; Meghan T. Turner (OTO Open, 2025)
Abstract Circulating tumor DNA (ctDNA) has been developed as a marker of tumor burden in human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPSCC). Inflammatory indices are also increasingly being used as prognostic surrogate markers in solid tumors, including head and neck cancers. The relationship between ctDNA levels and inflammatory indices has not been studied in HPV‐associated OPSCC. We hypothesize that higher levels of inflammation are associated with higher ctDNA levels. Herein, we demonstrate an association between high pretreatment ctDNA levels and specific inflammatory indices, which may be lower‐cost surrogate markers of high HPV ctDNA levels and may act as a surrogate marker for the body's immune response to HPV‐positive OPSCC.